Detecting axion stars with radio telescopes - Yang Bai; Yuta Hamada (Physics Letters B, 2018)
When axion stars fly through an astrophysical magnetic background, the axion-to-photon conversion may generate a large electromagnetic radiation power. After including the interference effects of the spacially-extended axion-star source and the macroscopic medium effects, we estimate the radiation power when an axion star meets a neutron star. For a dense axion star with 10−13M⊙, the radiated power is at the order of 1011W×(100μeV/ma)4(B/1010Gauss)2 with ma as the axion particle mass and B the strength of the neutron star magnetic field. For axion stars occupy a large fraction of dark matter energy density, this encounter event with a transient O(0.1s) radio signal may happen in our galaxy with the averaged source distance of one kiloparsec. The predicted spectral flux density is at the order of μJy for a neutron star with B∼1013 Gauss. The existing Arecibo, GBT, JVLA and FAST and the ongoing SKA radio telescopes have excellent discovery potential of dense axion stars.